Butterfly Diversity from Isolated Lowland Area: An Assessment in Langsa Urban Forest, Langsa, Aceh, Indonesia - Herlina Putri Endah Sari; Andri Yusman Persada; Wendy Achmmad Mustaqim; Kartika Aprilia Putri; Imti Yazil Wafa (Journal of Tropical Biodiversity and Biotechnology, 2023)
Langsa Urban Forest (LUF) is a 10-ha of the isolated urban forest in Langsa, Aceh, which is maintained to preserve urban biodiversity such as the butterfly. No recent study has been done in this area on butterfly biodiversity including the diversity and plant's potential for host and food plant sources. A one-month survey in July 2021 using the standard walk method on four transects was conducted. There are 36 species recorded during this study including 5 families, with Nymphalidae as the most abundant family and Leptosia nina as the most abundant species. Shannon-Wiener diversity index was used for this recent research with the value of H’ 1.78–2.78 and the Evenness index with scale 0.66–0.94. Most of the species have broad geographical ranges, with 3 of them restricted to the Indomalayan realm. There are 117 plants were recorded which 33 species supposed as host and food plants divided into 26 as host plants, 11 as food plants, and 4 for both. No specific plants threatened the collected butterflies, but it's important since providing diversity data.